Social system and the strategic entry of women entrepreneurs into the informal economy of Lagos State, South-West Nigeria - Olarenwaju, Olutayo Akinpelu; Olabisi, Yusuff Sherifat (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
The role of a social system in influencing the strategic entry of women into entrepreneurial activities and informal economy seems to have received relatively little academic attention inspite of the fact that entrepreneurship development is vital to economic growth, employment and quality of life. The focus of this paper is to examine the influence of social system in strategic entry of women into informal economic activities in Nigeria, using Yoruba women textile traders at Balogun market, Lagos State, South- West, Nigeria as a case study. The paper is anchored in Max Weber’s social action theory by. Utilized only qualitative method of data collection, eight focus group discussions and forty in-depth –interviews were used to collect information from the women participants who were purposively chosen. The data reveal that parents, family members, and social friends had great influence in determining the strategic entry of women into textile trading at Balogun market and the subsequent development of women entrepreneurial activities. Such findings are important with respect to policy formulation for women entrepreneurial development in the informal economy.